Walory i oferta turystyczna Wrocławia w opinii odwiedzających miasto - Marak, Janusz (Uniwersytet Wrocławski. Wydział, Prawa, Administracji i Ekonomii, 2013)
This paper presents the results of three surveys on the opinion of tourists about the touristic value of and attractions offered by Wrocław. The surveys differ as far as the aim, method and the scope of the subject, space and time are concerned.The results of all three surveys show a high level of satisfaction displayed by tourists who visited Wrocław. The city is perceived as one of the most attractive agglomerations in Poland. Even though each research had a different objective, a positive tendency is to be noticed. Over the period of 15 years (1997 – 2012) tourist assets of Wrocław have been strengthened and disadvantages have been minimalized. It proves that the initiatives taken by the city’s and regional authorities, as well as business offerto tourists were adequate
Keywords: Wrocław; turystyka; turyści